The Significance of Oath by Tāʾ in the Holy Qur’an - Al-Taweel, Emran Ahmed (Journal of Posthumanism, 2025)
This research aims to shed light on a specific style of oath in the Holy Qur'an-oath by the letter Tāʾ (التاء). This form of oath holds a unique status in Qur'anic usage, conveying specific meanings in the verses where it appears, differing at times from the grammatical discussions found in linguistic sources. The study explores whether the Tāʾ is an original element or a substitution for another letter and examines its semantic function within the Qur'anic text. Relying on the opinions of grammarians and various Qur'anic exegeses, the research seeks to uncover the true significance of oath by Tāʾ in the Qur'an and its contexts of usage.